2018
DOI: 10.1158/1538-7445.am2018-lb-092
|View full text |Cite
|
Sign up to set email alerts
|

Abstract LB-092: TAS120, a covalently-binding FGFR inhibitor (FGFRi), overcomes resistance to BGJ398 in patients with FGFR2 fusion positive cholangiocarcinoma

Abstract: Fibroblast growth factor receptor (FGFR) inhibitors are currently in clinical trials in a variety of cancers including lung, breast, urothelial, gastric, and uterine cancers and intrahepatic cholangiocarcinoma (ICC). The selective and potent ATP-competitive FGFRi BGJ398 has shown a 19% response rate in advanced refractory FGFR2-fusion positive ICC, but acquired resistance rapidly limits its efficacy. We previously reported the emergence of polyclonal FGFR2 kinase domain mutations in patients with ICC progressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Perhaps reassuringly, a few options already stand up at the horizon. For instance, F‐TKIs capable of binding to kinase‐mutated FFs are being developed . HSP90 inhibitors have also shown promising activity against FFs .…”
Section: Mechanisms Of Chemoresistancementioning
confidence: 99%
“…Perhaps reassuringly, a few options already stand up at the horizon. For instance, F‐TKIs capable of binding to kinase‐mutated FFs are being developed . HSP90 inhibitors have also shown promising activity against FFs .…”
Section: Mechanisms Of Chemoresistancementioning
confidence: 99%
“…Futibatinib (TAS-120), a third-generation irreversible pan-FGFR inhibitor, has since been shown to be active against multiple mutations conferring resistance to infigratinib on assessment of serial tumour and liquid biopsies and patient-derived ICC cells [69]. As futibatinib has been shown to provide patients with disease control in an early-phase trial [70], phase II evaluation is underway (FOENIX 101, NCT02052778). It has also been proposed that FGFR2-independent mechanisms, such as phosphatase and tensin homolog (PTEN) loss-of-function mutations, may contribute to secondary resistance and provide a rationale for dual inhibition of FGFR2 and PI3K/PTEN signalling pathways [68].…”
Section: Fgfr Gene Fusionsmentioning
confidence: 99%
“…A blockade of the hERG channel may cause drug-induced prolongation of the QT interval, which has become a major concern in drug discovery and development. To evaluate the cardiotoxicities of the candidates, we used a patch-clamp experiment to determine the hERG inhibitory activities of compounds 9, 10, 13, and 15, with cisapride 54 (19) as the positive control. As shown in Table 5, the hERG IC 50 values of most of the compounds are higher than 10 μM, and compounds 10 and 15 exhibited hERG IC 50 values higher than 40 μM.…”
Section: Investigation Of the Covalent Binding Mechanism Investigationmentioning
confidence: 99%
“…In a phase Ib/IIa study, a combination of 1 with either anastrozole or letrozole showed anti-tumor activity in advanced estrogen receptor-positive breast cancers resistant to aromatase inhibitors . In addition, a selective covalent FGFR inhibitor, 7 , has shown a tolerable safety profile and antitumor activity in patients with CCA harboring FGFR2 gene fusions and CCA patients with FGFR2 gene fusion resistance prior to the FGFR inhibitor 2 . ,, A phase II study of 7 with patients with intrahepatic CCA harboring FGFR2 gene fusions has been initiated. Despite the advances made in FGFR inhibitors, the road to clinical treatment of various diseases related to alterations of FGFR remains long and challenging.…”
Section: Introductionmentioning
confidence: 99%